Adaptation Learning Programme (ALP) - Harvey, Blane; Ensor, Jonathan; Garside, Ben; Woodend, John; Naess, Lars Otto; Carlile, Liz (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
CARE International launched the five-year Adaptation Learning Programme (ALP) for Africa in 2010, implemented in Ghana, Niger, Mozambique and Kenya, in partnership with local civil society and government institutions. The programme seeks to identify successful approaches to Community-Based Adaptation (CBA) for vulnerable communities through working directly with 40 communities as well as learning with other organisations practising CBA, and support incorporation of these approaches into development policies and programmes in the four countries and their regions in Africa.